9.05.015a CBC Xmas Show Sandy Morris, Rich Hollett, Brian Kenny and Don Walsh - Hollett, Rick Wayne; Walsh, Don; Morris, Sandy; Kenny, Brian
Sandy Morris, Rich Hollett, Brian Kenny and Don Walsh. An unofficial name I gave the show was "Merry Christmas and All that Jazz." This is just the music that we recorded in Studio F for the show.